Innovation Opportunities from e-Government Readiness Benchmark - Murasse, Carlos Mitsuru; Queiroz, Jamerson Viegas; da Silva, Christian Luis; Strauhs, Faimara do Rocio (European Scientific Journal, ESJ, 2018)
Research on e-government as well as its practice continues to bring challenges, especially for developing countries. The stage model is a frame of reference toward e-governance, where citizens are actively involved and the initiatives are collaborative in nature. Countries have been benchmarked on the e-government development and readiness indexes have been used to decision making. The aim of this paper is to investigate whether readiness benchmark on e-government can foster innovation. The result suggests that egovernment readiness indexes can foster some strategies related to technological or social innovation, and an innovation process measurement can improve the comprehension of the scenario.